Positive Choices: Addressing the evidence-practice gap in alcohol and other drug prevention. (30th September 2020) - Nepal, S; Stapinski, L; Newton, N; Grummitt, L; Lawler, S; Guckel, T; Lynch, S; Chapman, C; Teesson, M
Abstract: Issue: Alcohol and other drug (AOD) use during adolescence puts young people at risk of juvenile offending, poor educational outcomes, school dropout, and mental health issues. Since parents and school teachers are the primary source of contact for adolescents, it is important that they are equipped with accurate and up-to-date response strategies. There are a number of effective drug prevention strategies, however, they are not widely implemented. Description of the practice: To address this evidence-practice gap, the Positive Choices initiative was launched in 2015. Positive Choices supports implementation of evidence-based and prevention strategies through provision of training and a centralised information and resources portal for young people, their parents and teachers. The portal contains information factsheets and webinars and was developed in consultation with AOD experts and target users. Drug education resources and curriculum programs meeting pre-specified criteria for relevance, quality and evidence-base are listed in the resources database. Results: Positive Choices has been accessed by one-million Australian and international users. The most popular resources are videos, factsheets, webinars. In 2019, 71% parents and 65% teachers said that they would continue using the website. Half (54%) of school staff were not currently implementing evidence-based prevention strategies, of these 89% intended to shift to evidence-based practice after using Positive Choices. The majority of the users have said they would recommend the website to their colleagues and friends. Lessons: Positive Choices is effective in changing users' intentions to implement evidence-based strategies. Drug education programs need to engage parents and teachers if they are to be effective. Key messages: Positive Choices has increased users' awareness of evidence-based prevention strategies. Positive Choices has increased users' intentions to implement evidence-based prevention strategies.